Enabling socio-technical innovation bundles (STIBs) implementation in Ethiopia: a literature review of the policy context - Chakona, G.; Mapedza, Everisto D.; Nigussie, Likimyelesh; Nchanji, E.; Ketema, D. M.; Gartaula, H. N.; Joshi, Deepa; Puskur, R. (International Water Management Institute, 2024)
This report provides a comprehensive review of the intersection of agriculture, gender and socio-technical innovation bundles (STIBs) in Ethiopia, with a focus on understanding how policies, strategies and legislation can support the empowerment and resilience of women within the country's agrifood systems. STIBs are a comprehensive approach to tackling multifaceted challenges in agrifood systems by integrating technology with social and cultural innovations. Understanding how the innovations can be embedded into the existing policies within the agricultural sector to empower women and enhance gender equality, including women’s resilience and self-confidence is crucial. Agriculture remains the cornerstone of Ethiopia's economy, contributing 34% to the GDP and employing about 75% of the population. The report explores how aligning STIBs with Ethiopia's national development strategies can support key priority areas such as agricultural productivity, gender equality, food security, climate change adaptation, inclusive economic growth, technological advancement and education and training initiatives.